2020
DOI: 10.1073/pnas.1921512117
|View full text |Cite
|
Sign up to set email alerts
|

Spatial frequency tuning of motor responses reveals differential contribution of dorsal and ventral systems to action comprehension

Abstract: Understanding object-directed actions performed by others is central to everyday life. This ability is thought to rely on the interaction between the dorsal action observation network (AON) and a ventral object recognition pathway. On this view, the AON would encode action kinematics, and the ventral pathway, the most likely intention afforded by the objects. However, experimental evidence supporting this model is still scarce. Here, we aimed to disentangle the contribution of dorsal vs. ventral pathways to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Indeed, observing actions embedded in contexts that are congruent or incongruent with the unfolding kinematics, respectively, facilitated or inhibited discrimination performance and motor activation, as compared to observing actions embedded in an ambiguous context [14][15][16]. Notably, lower sensitivity to contextual information and higher reliance on the sensory evidence provided by kinematics were found in individuals with higher autistic traits [16], in particular in the domains of Social skills and Attention to details [16,36]. This points to an association between both social and non-social aspects of autistic traits and impairments in the integration of sensory evidence and contextual information.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, observing actions embedded in contexts that are congruent or incongruent with the unfolding kinematics, respectively, facilitated or inhibited discrimination performance and motor activation, as compared to observing actions embedded in an ambiguous context [14][15][16]. Notably, lower sensitivity to contextual information and higher reliance on the sensory evidence provided by kinematics were found in individuals with higher autistic traits [16], in particular in the domains of Social skills and Attention to details [16,36]. This points to an association between both social and non-social aspects of autistic traits and impairments in the integration of sensory evidence and contextual information.…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad consensus in the research literature that the processing of observed live actions in the AON provides observers with knowledge of what others are doing and that this is a key skill of social cognition [ 8 , 23 , 24 , 25 , 38 , 42 , 43 ]. There is, however, controversy about the properties of the knowledge conveyed by neural AON activities: is this knowledge only provided by AON activities, or is it dependent on conceptual and semantic processing [ 15 , 44 , 45 , 46 , 47 , 48 , 49 ]? Is it primarily related to understanding the goal of actions [ 3 , 5 , 15 ], or does it relate equally to several elements of actions, such as grips, movements of body parts, somatosensory processes, objects involved, or context [ 50 , 51 , 52 ]?…”
Section: Photographs Of Actions: What Makes Them Special Cues To Social Perceptionmentioning
confidence: 99%
“…Rizzolatti and Craighero [ 104 ] spoke of the “semantics” (p. 184) of the mirror neuron system. Action categorization is assumed to involve interactions between the AON and areas of the ventral visual stream [ 43 , 44 , 45 , 48 , 49 , 50 ]. These interactions run via neural bi-directional connections that give the AON access to conceptual and semantic information.…”
Section: Cognitive Products Of Processing Observed Actions In the Aonmentioning
confidence: 99%
See 2 more Smart Citations